Challenges of Islamic Da'wah in Bangladesh: The Christian Missions and Their Evangelization - Ali, Md Yousuf; Nurullah, Abu Sadat (IIUC Studies, 2009)
Although Bangladesh is the second largest Muslim populated country in the world, there are several challenges of Islamic da‘wah here. The Christian mission, taking the opportunity of people's poverty and distress, is evangelizing them through financial assistance and other means. The rapidly increasing number of conversion to Christianity among the tribal population is alarming. The missionary activities are spreading around the country, chiefly in the intellectual arena, in educational institutions, and in other aspects of life. The influence of it on the culture, education, religion and lifestyle of people results into converting people to the Christian ideology. Particularly the young generations are inclining towards this lucrative dogma of the new age. Media, both print and electronic, are propagating and claiming the banning of the da‘wah movement. In these situation, the Islamic da‘wah movements require to explore and implement new methodology to face the enormous challenges to prevent Bangladesh from becoming a Christian country in future. Keywords: Islamic da'wah, Christian mission, and evangelization. doi: 10.3329/iiucs.v4i0.2856 IIUC STUDIES Vol. - 4, December 2007 (p 87-108)